Defending Jacob [compact disc, unabridged] a novel - Landay, William (Blackstone Audio, Inc., 2012)
Andy Barber has been an assistant district attorney in his suburban Massachusetts county for more than twenty years. He is respected in his community, tenacious in the courtroom, and happy at home with his wife, Laurie, and son, Jacob. But when a shocking crime shatters their New England town, Andy is blindsided by what happens next: his fourteen-year-old son is charged with the murder of a fellow student. Every parental instinct Andy has rallies to protect his boy. Jacob insists that he is innocent, and Andy believes him. But as damning facts and shocking revelations surface, as a marriage threatens to crumble and the trial intensifies, and as the crisis reveals how little a father knows about his son, Andy will face a trial of his own--between loyalty and justice, between truth and allegation, between a past he's tried to bury and a future he cannot conceive.